2015
DOI: 10.4172/2169-0316.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Atomic and Crystalline Characteristics of Ceramic Oxide Nano Powders after Bio field Treatment

Abstract: Transition metal oxides (TMOs) have been known for their extraordinary electrical and magnetic properties. In the present study, some transition metal oxides (Zinc oxide, iron oxide and copper oxide) which are widely used in the fabrication of electronic devices were selected and subjected to biofield treatment. The atomic and crystal structures of TMOs were carefully studied by Fourier transform infrared (FT-IR) spectroscopy and X-ray diffraction (XRD) studies. XRD analysis reveals that biofield treatment sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
127
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 43 publications
1
127
0
Order By: Relevance
“…Biofield, the electromagnetic field that surrounds the living organism will provides regulatory and communication functions within the organism. Mr. Trivedi's biofield energy treatment was extensively studied in material science [11][12][13], agricultural science [14][15][16], in biotechnology [17]. It is reported in altering the susceptibility of antimicrobials of pathogenic microbes [18][19][20] and reduced the viral load in hepatitis C virus [21].…”
Section: Introductionmentioning
confidence: 99%
“…Biofield, the electromagnetic field that surrounds the living organism will provides regulatory and communication functions within the organism. Mr. Trivedi's biofield energy treatment was extensively studied in material science [11][12][13], agricultural science [14][15][16], in biotechnology [17]. It is reported in altering the susceptibility of antimicrobials of pathogenic microbes [18][19][20] and reduced the viral load in hepatitis C virus [21].…”
Section: Introductionmentioning
confidence: 99%
“…The Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that the Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramic in materials science [31][32][33], and improve the overall productivity of crops [34][35][36] as well as to modulate the efficacy of the various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…The objects always receive the energy and responding into useful way that is called biofield energy and the process is known as biofield treatment. Mr. Trivedi's unique biofield treatment (The Trivedi effect ® ) has been known to transform the structural, physical and thermal properties of several metals and ceramic in materials science [22][23][24], improved the overall productivity of crops [25,26], altered characteristics features of microbes [27][28][29] and improved growth and anatomical characteristics of medicinal plants [30,31].…”
Section: Introductionmentioning
confidence: 99%